The depressed child and adolescent - Goodyer, Ian M. (Cambridge ; New York : Cambridge University Press, 2001)
In this thoroughly revised and updated edition an international, interdisciplinary team of mental health experts draw together more recent research in the psychopathology of depression in young people. Combining theory and practice, the psychological, neurochemical and genetic causes are discussed and an account of the clinical characteristics and frequency of the condition is given. The key questions are fully addressed: the importance of life events and difficulties in the onset and continuation of depression; the efficacy of current psychological therapies and the role of medication; how depressed young people progress into adult life, and how depression arises and the effects it may exert on brain and behaviour during this crucial developmental period. This book will appeal to child psychiatrists and psychologists, developmental psychologists, neuroscientists and mental health professionals in clinical services.
Adolescent depression: neuroendocrine aspects / Stephen Sokolov and Stan Kutcher -- Suicidal behavior in adolescents / Erik Jan de Wilde, Ineke C.W.M. Kienhorst and René F.W. Diekstra -- Psychopharmacology of depressive states in childhood and adolescence / Eberhard Schulz and Helmut Remschmidt -- The psychotherapeutic management of major depressive and dysthymic disorders in childhood and adolescence: issues and prospects / Maria Kovacs and Joel T. Sherrill -- Natural history of mood disorders in children and adolescents / Richard Harrington and Bernadka Dubicka.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Depression in children; Depression in adolescence; Children; Depression, Mental; Depressive Disorder; Adolescent; Child; Depression; Dépression chez l'enfant.; Dépression chez l'adolescent.; Enfants; Dépression.; Enfance; children (people by age group); childhood; MEDICAL -- Pediatrics; HEALTH & FITNESS -- Children's Health; Depression, Mental; Children; Depression in adolescence; Depression in children; Depression; Jugend; Kind; Depressies (psychiatrie); Kinderen; Adolescenten